2022
DOI: 10.1038/s41598-022-06367-5
|View full text |Cite
|
Sign up to set email alerts
|

Congenital collagenopathies increased the risk of inguinal hernia developing and repair: analysis from a nationwide population-based cohort study

Abstract: Herein, we aimed to explore whether male patients with congenital collagen diseases had a higher risk of inguinal herniation than patients without these diseases. Data were retrospectively collected from the National Health Insurance Research Database of Taiwan. The study cohort included 1,801 male patients diagnosed with congenital collagen diseases based on the ICD-9 CM diagnostic codes; after propensity score matching, the control group comprised 6,493 men without congenital collagen diseases. The primary e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Some studies suggested that inguinal hernias are not just the result of a primary defect, but they could also arise as the consequence of a systemic disease regarding collagen distribution (35). This hypothesis could be also suggested if we take into account the genetic aspects of inguinal hernia disease (36), as well as the higher recurrence of inguinal hernia amongst patients diagnosed with congenital collagenopathy (37). This is why, in the following part, we will discuss some particularities of the extracellular matrix in inguinal hernia patients, as well as in obese patients.…”
Section: Methodsmentioning
confidence: 97%
“…Some studies suggested that inguinal hernias are not just the result of a primary defect, but they could also arise as the consequence of a systemic disease regarding collagen distribution (35). This hypothesis could be also suggested if we take into account the genetic aspects of inguinal hernia disease (36), as well as the higher recurrence of inguinal hernia amongst patients diagnosed with congenital collagenopathy (37). This is why, in the following part, we will discuss some particularities of the extracellular matrix in inguinal hernia patients, as well as in obese patients.…”
Section: Methodsmentioning
confidence: 97%
“…In performing the literature review, it was found one systematic review and meta-analysis [ 22 ], one systematic review [ 23 ], two narrative reviews [ 24 , 25 ], one clinical trial [ 26 ], eight observational studies [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ], and one case series [ 35 ], that discussed the relationship between some risk factors, interventions and outcomes in the management of inguinal hernia.…”
Section: Risk Factors Interventions and Their Impact On Functional An...mentioning
confidence: 99%
“…It is presumed then, that the higher the pain score and neuronal involvement, the slower and more difficult will be the long-term post-operative pain recovery process. Recently, Chang et al [ 27 ] published an interesting study, where they studied 1801 men with a congenital collagenopathy vs. a control group (6493 men), showing that the risk of developing inguinal hernia was significantly higher in the group with the pathological history (HR 2.237; 95% CI, 1.646–3.291, p < 0.001), compared to the control group [ 27 ]. This risk is much higher in those under 18 years of age (HR 3.040; 95% CI, 1.819–5.083, p < 0.001), compared to any other age group.…”
Section: Risk Factors Interventions and Their Impact On Functional An...mentioning
confidence: 99%
See 2 more Smart Citations